2015
DOI: 10.1016/j.ejvs.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antiplatelet Therapy Prior to Expedited Carotid Surgery Reduces Recurrent Events Prior to Surgery without Significantly Increasing Peri-operative Bleeding Complications

Abstract: Early introduction of dual antiplatelet therapy was associated with a significant reduction in recurrent neurological events and spontaneous embolization prior to CEA, without incurring a significant increase in major peri-operative bleeding complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…13 The protective neurologic effects of clopidogrel have also been suggested for urgent CEA 14 and in other series of patients with symptomatic carotid stenosis. 15,16 Furthermore, emerging evidence by Batchelder et al 17 suggests that initiating clopidogrel in patients who have recently suffered a TIA associated with 50% to 99% carotid artery stenosis can significantly reduce the risk of recurrent neurologic events before definitive CEA, thus recommending its use in this presumptively vulnerable patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The protective neurologic effects of clopidogrel have also been suggested for urgent CEA 14 and in other series of patients with symptomatic carotid stenosis. 15,16 Furthermore, emerging evidence by Batchelder et al 17 suggests that initiating clopidogrel in patients who have recently suffered a TIA associated with 50% to 99% carotid artery stenosis can significantly reduce the risk of recurrent neurologic events before definitive CEA, thus recommending its use in this presumptively vulnerable patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the clearly demonstrated protective perioperative neurologic effects independent of symptom status, we recommend dual therapy in symptomatic patients to reduce the risk of preoperative stroke after initial symptoms, as others have shown. 17 We also recommend meticulous attention to hemostasis when performing CEA in patients on dual therapy due to the increased risk of reoperation for bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of neurological events prior to CEA declined from 29 to 2.5% after implementation of a “best medical therapy” protocol. A study from the UK also found that in patients with symptomatic carotid stenosis, dual antiplatelet therapy reduced the number of brain microemboli detected with TCD 18 . This study also found that 0 out of 100 patients awaiting CEA experience a recurrent stroke while awaiting revascularization.…”
Section: Symptomatic Carotid Stenosismentioning
confidence: 94%
“…49 Specific to carotid disease, it has been shown that initiation of DAPT in patients with recently symptomatic carotid stenosis leads to decreased transcranial Doppler-detected microembolization (which are associated with TIA/Stroke risk) 50 , and recurrent neurological events. 51 Early initiation of DAPT should be considered after symptom onset, though this must be weighed against bleeding risk of any planned revascularization. 4, 52…”
Section: Developments and Controversies In Symptomatic Carotid Smentioning
confidence: 99%